Linguagens urbanas e modernidade na Babel amalucada: cartas caipiras em periódicos paulistanos (1900-1926) - Rodrigues, Beatriz [UNESP] (2015)
This work deals with the analysis of the caipira dialect, found in São Paulo‟s periodicals of the years 1900-1926, which contains glimpses of daily life in the capital, bringing forward many of the transformations experienced by their inhabitants. The ones who wrote it, while representing the modern city, ended up tracing a profile of the country person too. The caipira's images that were built are related to matters of brazilian identity, and establish a dialog with the literary productions of that period, especially the ones by Cornélio Pires. The letter like style, the text's arrangement in verses and the use of pseudonyms were some of the characteristics of this kind of production, which, along with the macaronic texts, pointed to the insertion of a more colloquial language in the press. It was through a relaxed and comic discourse that the letters represented the city as well as the country person, while also being a part of that reality as a cultural practice